Effects of conventional physical therapy with and without proprioceptive neuromuscular facilitation on balance, gait, and function in patients with Parkinson’s disease - Tahzeeb Mazhar; Ayesha Jameel; Faiza Sharif; Momna Asghar (Journal of the Pakistan Medical Association, 2023)
The study was conducted at University of Lahore Teaching Hospital and Sir Ganga Ram Hospital, Lahore, using non-probability convenience sampling. Thirty-eight patients of Parkinson’s disease were allocated by randomisation into two groups. PNF Group (group A) performed proprioceptive neuromuscular facilitation incorporated with conservative treatment, while for the conventional therapy group (group B) only conservative treatment was followed. Berg Balance Scale, Freezing of Gait questionnaire, and Functional Independence measure were used as outcome measuring tool. Berg balance scale values were significantly improved in group A at 12th week as compared to group B. Freezing of gait and functional independence was more significantly reduced in group A at sixth and 12th week as compared to group B. Hence, it is concluded that Proprioceptive neuromuscular facilitation combined with routine treatment regime improves balance, gait, and function of Parkinson’s patients more effectively as compared with routine treatment protocol only.